Bessel's polynomial fitting for electrospun polyacrylonitrile/polyaniline blend nanofibers based ammonia sensor - Anwane, Rajashree S.; Kondawar, Subhash B.; Late, Dattatray J. (Materials Letters, 2018)
In the present paper, we report the fabrication of electrospun polyacrylonitrile/polyaniline (PAN/PANI) blend nanofibers by electrospinning and polymerization and Bessel's polynomial model applied for its ammonia sensing characteristics. As-fabricated PAN/PANI blend nanofibers were characterized by scanning electron microscopy and Fourier transform infrared spectroscopy for the confirmation of fibers with nanoscale and blends of PAN and PANI. The semiconducting behavior of the PAN/PANI blend nanofibers was found to respond quickly towards ammonia gas. Sensitivity of the blend was obtained at near room temperature for different concentrations of ammonia. Bessel's polynomial function was found to be well fitted with the experimental data for the response towards ammonia gas. (C) 2018 Elsevier B.V. All rights reserved.